Critical appraisal of determinant factors of an extensive oral squamous cell carcinoma - Report of case - Daroit, Natália Batista; Candreva, Monique Santanna; Freire, Nathália de Almeida; Antero, Sarah Aparecida Ferreira; Rados, Pantelis Varvaki; Israel, Mônica Simoes (Journal of Oral Diagnosis, 2018)
Introduction: Oral squamous cell carcinoma (OSCC) is the most frequently occurring oral malignant neoplasm. Early diagnosis is essential for determining the treatment and prognosis of OSCC. Objective: The aim of this study was to report a case of an extensive OSCC, to discuss factors involved in the diagnosis of advanced lesions and to clarify diffi- culties experienced in referring patients with OSCC for treatment to a healthcare system. Methods: The study included male patients aged 50 years who were chronic alcoholic and tobacco smokers, who had severe trismus, and who presented with ulceroprolifera- tive growth with indurated raised margins, involving the left palate and lower gingiva, extending into the buccal mucosa, and overlying the skin. Results: An incisional biopsy confirmed the diagnosis of OSCC, and the patient was referred for treatment. Conclusions: The factors that delay the diagnosis of OSCCs are misinformation, self-care negligence, socioeconomic aspects, inappropriate oral mucosa examinations, unknown oral diseases, and failure to obtain a conclusive diagnosis and forwarding the patient to the treatment.